Porosity Analytical Tool Based on Infrared (IR) Images of Concrete - Shera Anak Gilbert, Shera Anak Gilbert; Andri Kusbiantoro; Amalina Hanani Ismail (Journal of Advanced Industrial Technology and Application, 2022)
Images analysis techniques are gaining popularity in the studies of civil engineering technology. However, the current image analysis methods often require advanced machinery and strict image acquisition procedures, which may be challenging in actual construction practices. Therefore, this study develops a simplified image analysis technique that uses the FLIR ONE infrared camera to capture the concrete surface compatible with the Infrared (IR) concrete images. The infrared image is then converted into contour plot images using MATLAB software and analysed using AutoCAD to determine the thermal colour’s diameter on the infrared images. This study focuses on the white and yellow colours. The yellow thermal colour is the outer of the Thermal Diameter Reduction (TDR) rate of concrete, while the white thermal colour is the inner due to the highest temperature. However, to determine the accuracy of the MATLAB image processing, additional image editing is performed by utilising image exposure editing in conjunction with AutoCAD. The result from MATLAB was then gathered and compared to the image exposure editing to find the correlation between porosity, compressive strength and TDR rate of concrete. Experimental results showed that porosity affected the TDR rate with reliable accuracy of 90.00 %, compressive strength 70.00 %, and concrete density 60.00 %. The result analysis shows that concrete with high characteristic strength is in a less porous state, which means it is denser and transfers heat slowly to the surface, thus making the TDR rate value of the concrete minimum